2012
DOI: 10.1016/j.juro.2012.01.068
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes of Pregnancy Following Surgery for Stress Urinary Incontinence: A Systematic Review

Abstract: Purpose Although few data have been published on the safety of childbearing after surgery for stress urinary incontinence, a large proportion of physicians recommend that women wait to complete childbearing before pursuing surgical treatment for stress urinary incontinence. We systematically reviewed the available literature to examine the safety of pregnancy after stress urinary incontinence surgery, and to measure the effect of such pregnancy on continence outcomes. Materials and Methods The review was con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(7 citation statements)
references
References 27 publications
0
6
0
1
Order By: Relevance
“…103 However, the scientific evidence to support this notion, as well as, recommendations to perform an elective caesarean section if pregnancy occurs after a MUS procedure, are based on small case series including sample sizes of 32 to 54 women. [104][105][106][107] The rate of SUI in these series have ranged between 70-80% in women having given birth after MUS surgery. None of the studies included a control group (non-exposed women) and the duration of follow-up was limited.…”
Section: Childbirth After Mid-urethral Sling Surgerymentioning
confidence: 89%
See 1 more Smart Citation
“…103 However, the scientific evidence to support this notion, as well as, recommendations to perform an elective caesarean section if pregnancy occurs after a MUS procedure, are based on small case series including sample sizes of 32 to 54 women. [104][105][106][107] The rate of SUI in these series have ranged between 70-80% in women having given birth after MUS surgery. None of the studies included a control group (non-exposed women) and the duration of follow-up was limited.…”
Section: Childbirth After Mid-urethral Sling Surgerymentioning
confidence: 89%
“…Previous studies has shown a SUI prevalence of 20 % in women with childbirth after a MUS procedure. 104,106 A Swedish study on long-term outcomes after MUS procedures, without subsequent deliveries, reported a durable cure rate of up to 90 %. 128 A 10 percentage-points difference could be considered clinically relevant.…”
Section: Power Calculationmentioning
confidence: 99%
“…The original MUS operations were developed and studied in a Nordic co-work [ 12 ], and thus it is likely that similar technique and indications in the Nordic countries explain the comparable results. However, smaller case series from other countries also show MUS to be effective after subsequent childbirth [ 13 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…This showed that 10 of the 12 delivered vaginally and nine of the 11 delivered by caesarean were continent at 2–36 months, giving a recurrence of 20% . A recent systematic review of outcomes of pregnancy following surgery for stress urinary incontinence showed that the incidence of postpartum stress urinary incontinence ranged from 5 to 18% after caesarean delivery and 20 to 30% after vaginal delivery . The authors commented on the limited studies available in the literature, and only in the form of case reports, case series and physicians' surveys, and stated that a formal analysis between the risk after caesarean and vaginal delivery could not be performed with the limited data available.…”
Section: Discussionmentioning
confidence: 99%